HUBUNGAN ANTARA KECERDASAN SPIRITUAL DENGAN KEJUJURAN SISWA KELAS IX SMP 15 SEMARANG - Ayu Wulandari; Tri Suyati; Padmi Dyah Yulianti (CV. Denasya Smart Publisher, 2024)
This research is motivated by identifying the relationship between spiritual intelligence and honesty. There are still many students who are less than honest, such as discussions when taking exams, discussions with friends. This type of research is quantitative research with an expo facto analysis design. The population of this research was class IX students at SMP 15 Semarang with a total of 265 students. Class IX I with a total of 34 students was used for tryouts. The sample for this research was 3 classes from 8 population classes with a total of 100 students using a cluster random sampling technique. The data collection tool used is a research scale in the form of a questionnaire. Based on the table, the sig value is obtained. (2-tailed) is <0.001 <α value (0.05), then H0 is rejected, this means that there is a relationship between spiritual intelligence and honesty in class IX students of SMP 15 Semarang. Apart from significance, it can be seen that the correlation value is 0.197, which means that there is a positive relationship between spiritual intelligence and honesty of class IX students at SMP 15 Semarang. There is a positive direction of relationship, which means the two variables go in the same direction, increasing or decreasing.